A novel turn-on type fluorescent probe with a large red-shift based on TPE for detection of F−. (17th December 2022) - Yang, Jianing; Yuan, Xiaowan; Wang, Yilan; Liu, Hongliang; Pu, Shouzhi
Abstract: A tetraphenylethylene derivative with AIE properties was successfully synthesized, displayed a large Stokes shift (Δ λ = 123 nm) in THF. TBIP could also be used as a turn-on fluorescent probe for fluoride ion recognition, with a large red-shift (101 nm), rapid response, and excellent selectivity. The limit of detection (LOD) was calculated and derived as 0.006 μM in solvent, which was far lower than the maximum pollutant level of fluorine ion in drinking water, and fluorescence color changing from blue-purple to yellow. The application research indicated that the sensor could detect F − in natural water sensitively, and could prepare qualitative test strips for fluorine ion detection. Graphical abstract: TBIP, a compound based on tetraphenylethylene and imidazolium phenanthroline was synthesized, which had significant aggregation-induced emission (AIE) properties. In addition, TBIP could also be used as a "turn on" fluorescent probe to detect F − in acetonitrile solution, and had been successfully applied to test paper strips and natural water samples. Image 1 Highlights: A tetrabenylbenzene derivative with AIE properties was successfully synthesized, displayed a large Stokes shift (Δ λ = 123 nm) in THF. TBIP could also be used as a "turn on" fluorescent probe for fluoride ion recognition, with a large red shift (101 nm). TBIP had good selectivity, low detection limit, and has been successfully applied to test strips and natural water samples.